MENINGKATKAN MINAT MEMBACA MELALUI METODE BERCERITA DENGAN BIG BOOK ANAK USIA 5-6 TAHUN DI PAUD BUNDA SUWARNI KECAMATAN MARPOYAN DAMAI KOTA PEKANBARU - Leni Leni; Tri Utami; Enda Puspitasari (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrat : The purpose of this study are as follows: 1) To determine the reading In Children Aged 5-6 Years in early childhood Suwarni Bunda District of Marpoyan Peace Pekanbaru. 2) To find out how to improve the behavior of Interests Reading Children Aged 5-6 Years to implement the method of storytelling with the Big Book in early childhood Suwarni Bunda District of Marpoyan Peace Pekanbaru. 3) Improved reading In Children Aged 5-6 Years through storytelling with Big Book in early childhood Suwarni Bunda District of Marpoyan Peace Pekanbaru. This research subject Ra child Mother Suwarni Pekanbaru with the number of children as many as 11 children consisting of six men and five daughters. Data was collected using observation sheet interest in reading, observation sheet activities of teachers and students. Collecting data using observation and documentation. The survey results revealed that the magnitude of the increase in interest in reading in children aged 5-6 years in early childhood Mother Suwarni Pekanbaru as of prior to the first cycle of action to an increase of 32.8%. While the increased interest in reading in children from the first cycle to the second cycle by 51%, and overall improvement of interpersonal intelligence of initial data to the second cycle of 99%.Keywords: Reading Interest, storytelling, big book